2020
DOI: 10.13031/trans.13912
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Infrared Canopy Temperature Data in Relation to Soil Water-Based Irrigation Scheduling in a Humid Subtropical Climate

Abstract: HighlightsCorn response to irrigation was influenced by the precipitation distribution in 2018 and 2019, and that impacted the response of CWSI as an irrigation scheduling signaling method.CWSI was sensitive to changes in soil water storage, increasing due to crop evapotranspiration and decreasing after a precipitation or irrigation event.In 2018, both seasonal CWSI and yield were not different among the irrigation treatments, while in 2019, seasonal CWSI and yield were all statistically different among the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Advances in irrigation technology [e.g., sensors, irrigation controllers, unmanned aerial systems (UAS)] and its adoption and the availability of innovative research, extension, and education programs in irrigation science were key factors in the progress of irrigation management in the U.S. during the past decade. Seven journal articles from this ASABE Special Collection are discussed in this section, but ten additional articles (Andrade et al, 2020a(Andrade et al, , 2020bCardenas et al, 2020;Conger and Dukes, 2020;Dukes, 2020;Evett et al, 2020b;Lena et al, 2020;O'Shaughnessy et al, 2020;Stone et al, 2020;Sui et al, 2020) discussed in other sections of this article easily overlap with this topic.…”
Section: Technology and Innovation (Sensors Technology Usage And Adoption Extension/education)mentioning
confidence: 99%
See 2 more Smart Citations
“…Advances in irrigation technology [e.g., sensors, irrigation controllers, unmanned aerial systems (UAS)] and its adoption and the availability of innovative research, extension, and education programs in irrigation science were key factors in the progress of irrigation management in the U.S. during the past decade. Seven journal articles from this ASABE Special Collection are discussed in this section, but ten additional articles (Andrade et al, 2020a(Andrade et al, , 2020bCardenas et al, 2020;Conger and Dukes, 2020;Dukes, 2020;Evett et al, 2020b;Lena et al, 2020;O'Shaughnessy et al, 2020;Stone et al, 2020;Sui et al, 2020) discussed in other sections of this article easily overlap with this topic.…”
Section: Technology and Innovation (Sensors Technology Usage And Adoption Extension/education)mentioning
confidence: 99%
“…Nearly 30% of the total irrigated land area in the U.S. is located in the eastern humid states, and the area continues to increase (USDA-NASS, 2018). Overall, eight journal articles for this ASABE Special Collection were related to agricultural irrigation in the humid region, with three articles specifically discussed in this section (Leib et al, 2020;Lena et al, 2020;Reinhart et al, 2020). The other five articles were discussed in the Technology and Innovation section (Chiu and Reba, 2020;Henry, et al, 2020;Lo et al, 2020), the Irrigation Systems section (Reba and Massey, 2020), and the Irrigation Management section (Zamora-Re et al, 2020).…”
Section: Irrigation In the Humid Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…Irrigation water is key to crop production due to its contribution to attainable yield, role on nutrient uptake (Sigua et al, 2017), and mitigation of heat and water stress to the crop (Lena et al, 2020;Mondaca-Duarte et al, 2020). Even with the importance of irrigation in agriculture, there are still many challenges associated with irrigation adoption, such as competition for freshwater with urban areas and industry, the increased irrigation demand for bioenergy crops, and lack of adoption of efficient irrigation systems and best irrigation management practices (USDA-ERS, 2019;WWAP, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Some irrigation specialists consider MAD as 50% but this value should be adjusted based on crop type, climate, soil type, and the irrigator's knowledge (Rogers, 2012). Soil sensor data allows the irrigation operator to track SWS so it can be maintained above the irrigation threshold (MAD level) to prevent crop water stress and subsequently yield losses (Lena et al, 2020;Rogers, 2012). Several authors have reported multiple benefits from the use of this approach.…”
Section: Introductionmentioning
confidence: 99%